Character Education in History Learning at MAN Insan Cendekia, Palu City - Alim, Nur; Misnah; Ratu, Bau (Kirana Publisher (KNPub), 2024)
This study aims to (1) explain the concept of character education at MAN Insan Cendekia, Palu City, (2) explain the application of character education in history learning for class XI IPS Al-Kautsar students at MAN Insan Cendekia, Palu City, and (3) explain the character values applied in history learning for class XI IPS Al-Kautsar students at MAN Insan Cendekia, Palu City. This study is a type of qualitative research. Data collection techniques use observation, interviews, and documentation. Data analysis uses data reduction techniques, data presentation, and drawing conclusions. The results of the study indicate that (1) Character education implemented at MAN Insan Cendekia, Palu City refers to the curriculum policy at the Boarding School- based Madrasah. School and Vision and Mission of MAN Insan Cendekia Palu City. (2) The implementation of character education in history learning for class XI IPS Al-Kautsar students at MAN Insan Cendekia Palu is carried out through the management of planning, implementation, and evaluation of character education for students in the class. (3) The character values applied in history learning for class XI IPS Al-Kautsar students at MAN Insan Cendekia Palu collectively contain 18 character values of cultural education and national character as stipulated by the Minister of National Education in 2010.